Dynamic Akt/mTOR Signaling in Children with Autism Spectrum Disorder - Onore, Charity; Yang, Houa; Van de Water, Judy; Ashwood, Paul (Frontiers in Pediatrics, 2017)
Autism Spectrum disorder (ASD) is a behaviorally defined disorder affecting 1 in 68 children. Currently, there is no known cause for the majority of ASD cases nor are there physiological diagnostic tools or biomarkers to aid behavioral diagnosis. However, sibling concordance suggests a strong genetic component to this disorder. Whole-genome linkage studies, genome wide association studies, copy number variation screening and SNP analyses have identified several ASD candidate genes, but which vary greatly among individuals and family clusters, suggesting that a variety of genetic mutations may result in a common pathology or alter a common mechanistic pathway. Among the most highly associated single gene mutations in ASD are those in the Akt/mTOR pathway, including FMR1 (Fragile X), TSC1 or TSC2 (Tuberous Sclerosis), PTEN (Cowden’s Syndrome), and NF1 (Neurofibromatosis type 1). The Akt/mTOR pathway is involved in many cellular processes including synaptic plasticity and immune function that can alter neurodevelopment. We also tested the hypothesis that primary T cell could be useful as a relatively non-invasive test to assess dynamic Akt/mTOR signaling that would not be capable in post-mortem tissues. To address this, we examined activity of the Akt/mTOR pathway in primary cells isolated from young children with ASD and typically developing controls of the same age. Phosphorylation levels of insulin receptor substrate-1 (IRS1), phosphatase and tensin homolog (PTEN), tuberin (TSC2), Akt, glycogen synthase kinase 3 (GSK3)α, GSK3β, mammalian target of rapamycin (mTOR), p70S6 kinase (p70S6K), ribosomal protein S6 (RPS6), and extracellular receptor kinase (ERK) were measured in all subjects. We observed higher activity of mTOR, ERK, p70S6K, as well as lower activity of GSK3α (p=0.050) and TSC2 in cells from children with ASD, which suggests higher activity in the Akt/mTOR pathway. ASD subjects also exhibited higher activity of the Akt/mTOR pathway than controls after 15 minutes and 45 minutes of cellular activation. In this article, we describe a phosphorylation pattern in the general/idiopathic ASD population of high Akt/mTOR pathway activity, which had been previously described for known ASD associated mutations, and may suggest a common pathological pathway of interest for ASD.